Underwater archaeological survey in the area of the islets of Sv. Fumija and Kraljevac near the island of Čiovo (In situ, 2024)
Systematic underwater archaeological survey was carried out in the area of the islets of Sv. Fumija and Kraljevac, which are located along the southern coast of the island of Čiovo. A coastal construction of an ancient villa, a chert bed, and individual finds of ancient amphora fragments were found, distributed over a wider area of the examined segment.
Keywords: Čiovo; Sv. Fumija; Kraljevac; underwater archaeological survey